Sensitisation study of normalized 316L stainless steel (2010)
"Austenitic stainless steels with excellent corrosion resistance and good weldability have wide applications in industry. These iron-based alloys contain a high level of chromium which form protective oxide film on the surface hence resisting corrosion. The oxide film regenerates when damaged, making the steel 'stainless'. However, carbide precipitation due to a welding process or heat treatment can cause the occurrence of chromium-depleted zones at the boundaries, leading to a phenomenon known as sensitisation, in which the depleted zones become the focus of the intense corrosion. The present work was concerned with the study of the sensitization and desensitisation of 316L steel at the normalizing temperatures of 750- 9500 C and soaking times of 0.5, 1, 2 and 8 hrs. 316L stainless steel was observed to be sensitized when heated to 750- 8500 C and held for short soaking times of 0.5 – 2hrs before normalizing. Increasing soaking times at these temperatures to 8 hrs triggered the desensitization process which was fully accomplished at 7500 C but ongoing at 800 and 8500 C. At 9000 C, sensitization did not occur at 30 mins soaking time but observed at soaking times of 1 and 2hrs. At a longer soaking time of 8 hrs, there was full desensitization. At 9500 C, sensitization was already observed at 30 mins. Soaking time and desensitization was observed to be in progress at 1 and 2 hrs soaking time. By 8 hrs there was full desensitization. Thus it was observed that at 9500 C, diffusion of Cr was thermally aided making desensitization fast. The hardness of normalized 316L stainless steel was also observed to decrease with soaking time and normalization temperature "